Tinjauan Filosofis terhadap Perubahan Batas Usia Perkawinan dalam Undang-Undang Nomor 16 Tahun 2019 tentang Perubahan Atas Undang-Undang Nomor 1 Tahun 1974 tentang Perkawinan - Abdul Hamid; Syukri Iska; Eficandra Eficandra; Zulkifli Zulkifli; Sri Yunarti (Al-Qisthu: Jurnal Kajian Ilmu-Ilmu Hukum, 2021)
This article examines changes in the marriage age limit for women in Indonesia, from sixteen to nineteen years. This change was made through Law Number 16 of 2019 concerning Amendments to Law Number 1 of 1974 concerning Marriage. This study examines how the philosophical review of changes in the age limit for marriage is in the health, sociological, psychological, educational, and constitutional aspects. For this purpose, this study uses the library research method. The primary data source is Law Number 16 of 2019, while secondary data is the academic text of Draft Law Number 16 of 2019. This study shows that, firstly, in terms of health, changing the age limit for marriage maintains the safety of girls’ lives. Second, on the sociological aspect, this change provides opportunities for women to prepare themselves to enter social interaction in society. Third, on the psychological part, this change protects women’s psyche, mentality, and mind. Fourth, in education, this change is to provide opportunities for women to be freer to study. Fifth, on the constitutional aspect, this change provides equal rights for men and women in obtaining legal protection and justice.